PENGARUH LATIHAN INTERVAL DAN LATIHAN CONTINUE TERHADAP PENINGKATAN VO2MAX RENANG GAYA KUPU-KUPU PADA ATLET SULAWESI SELATAN - Kurnia, Kurnia; Burhanuddin, Sudirman; Ihsan, Andi; Kamaruddin, Ilham; Hudain, Muh Adnan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze and compare the effectiveness of interval training and continuous training in improving aerobic capacity (VO₂Max) among butterfly stroke swimmers from South Sulawesi Province, Indonesia. A quasi-experimental method with a pretest-posttest control group design was employed. The participants consisted of 30 butterfly stroke athletes who were equally assigned to two intervention groups: interval training and continuous training, with 15 athletes in each group. VO₂Max was measured before and after the intervention using a respirometer. Data were analyzed using paired-sample t-tests to examine within-group changes and independent-sample t-tests to compare differences between groups at a significance level of 0.05. The results demonstrated that interval training significantly improved VO₂Max from a mean value of 3.816 to 4.048 L/min (Δ = 0.232; p < 0.001). Similarly, continuous training produced a significant increase in VO₂Max from 3.805 to 4.027 L/min (Δ = 0.222; p < 0.05). Although both training methods yielded positive effects on aerobic capacity, the between-group comparison revealed no statistically significant differences at either the pretest (p = 0.891) or posttest (p = 0.804). In conclusion, both interval training and continuous training are equally effective in enhancing VO₂Max among butterfly stroke swimmers, with no significant difference in their effectiveness. These findings suggest that coaches may flexibly incorporate either training approach into conditioning programs to optimize the aerobic capacity of competitive butterfly swimmers.